2023
DOI: 10.1371/journal.pone.0285470
|View full text |Cite
|
Sign up to set email alerts
|

Could secondary flows have made possible the cross-strait transport and explosive invasion of Rugulopteryx okamurae algae in the Strait of Gibraltar?

Abstract: Presently, the Strait of Gibraltar is undergoing an unprecedented invasion of the alien alga Rugulopteryx okamurae of North Pacific origin. According to the scarce literature, the algae first settled in the south shore, probably following commercial exchanges with French ports where it was accidentally introduced together with Japanese oysters imported for mariculture. There is no certainty, however, that the algae first colonized the south shore of the Strait and, from there, spread to the north. It could wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…The presence of R. okamurae in Sicily may have two explanations that are not exclusive, but rather, on the contrary, synergistic. On the one hand, the species may have arrived in the form of large accumulations of biomass transported by currents, as already observed in the Alborán Sea (García-Lafuente et al 2023;Mateo-Ramírez et al 2023) and suggested to explain the presence of the species in Madeira (Bernal-Ibáñez et al 2022). In other words, marine currents may be facilitating the longdistance dispersal of the species, allowing the arrival of large amounts of biomass that either have been detached from populations established in remote areas, or that have grown in suspension in the water column until it was dumped on the beach.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…The presence of R. okamurae in Sicily may have two explanations that are not exclusive, but rather, on the contrary, synergistic. On the one hand, the species may have arrived in the form of large accumulations of biomass transported by currents, as already observed in the Alborán Sea (García-Lafuente et al 2023;Mateo-Ramírez et al 2023) and suggested to explain the presence of the species in Madeira (Bernal-Ibáñez et al 2022). In other words, marine currents may be facilitating the longdistance dispersal of the species, allowing the arrival of large amounts of biomass that either have been detached from populations established in remote areas, or that have grown in suspension in the water column until it was dumped on the beach.…”
Section: Discussionmentioning
confidence: 80%
“…Its limit in the Mediterranean is currently found on the coast of Marseilles, in France (Ruitton et al 2021). The species has a high capacity for vegetative proliferation as well as for dispersal, which gives it a high capacity to produce large amounts of biomass that can be moved by currents (García-Lafuente et al 2023;Mateo-Ramírez et al 2023) or helped by human vectors such as fishing or maritime transport (MITECO 2022), and which can end up forming important wracks on the coasts. The seaweed's ability to fast proliferation is causing serious concern, because it greatly impacts both native natural communities (seagrasses and marine forests), reducing their extension and diversity (García Gómez et al 2020, and human activities such as fishing and tourism, with losses of millions of euros across various sectors (CIRCABC 2020; MITECO 2022).…”
Section: Introductionmentioning
confidence: 99%